EXTH-52. GLIOBLASTOMA-TARGETING AUTOLOGOUS INDUCED NEURAL STEM CELL THERAPY: EVALUATING SAFETY, TOXICITY, PERSISTENCE, AND TRANSPLANT METHODS IN A POST-SURGICAL CANINE MODEL - Bomba, Hunter (Neuro Oncol, 2020)
BACKGROUND: Glioblastoma patient survival statistics have remained unchanged for more than three decades. Despite tumor resection and chemoradiotherapy, recurrence is inevitable. Moreover, the invasive behavior of glioblastoma confounds treatment. To improve patient survival statistics, a targeted therapy that can home to distant tumor foci is desperately needed. Induced neural stem cells (iNSCs) armed with cytotoxic payloads have proven efficacious against human xenograft models of glioblastoma. To further propel iNSCs to human clinical trials, we investigated the safety, toxicity, and persistence of iNSCs in a canine model. METHODS: Autologous iNSCs generated from the skin of four non-tumor-bearing, purpose-bred, male beagles were engineered to express TRAIL and thymidine kinase (TK). iNSCs were loaded with ferumoxytol to facilitate MRI-tracking. Canines were divided into two cohorts to denote iNSC administration route: scaffold encapsulation or intracerebroventricular (ICV). Two dose levels were investigated: 1′10(6) iNSCs/kg or 3′10(6) iNSCs/kg. The scaffold cohort received a single dose of iNSCs while the ICV cohort received three doses of iNSCs via a Rickham reservoir. To activate TK, canines were administered valganciclovir. Canine health was assessed via neurological exams, MRI, and serial blood, urine, and CSF analyses. RESULTS: No acute injection reactions were observed. Three of four canines exhibited surgery-induced blindness. Urine and CSF analyses were unremarkable. Unexpectedly, blood analyses showed transient neutropenia. Hypodense signal was observed on all MRI sequences through endpoint. Post-mortem histopathology of the spleen, liver, and lung were unremarkable. As expected, brain tissues exhibited gliosis, fibrous thickening, and inflammation. Spinal cords exhibited acute hemorrhaging, attributed to perimortem CSF draws. Surprisingly, significant testicular degeneration was observed; this was confirmed to be caused by valganciclovir. In conclusion, iNSCs exhibit limited toxicity and warrant further exploration. FUTURE DIRECTIONS: Prospective studies will investigate the efficacy of autologous iNSCs in a spontaneous canine glioma model in preparation for human clinical trials.